Prevalence, Awareness, and Treatment of Isolated Diastolic Hypertension: Insights From the China PEACE Million Persons Project - Shiwani Mahajan; Danwei Zhang; Siyun He; Yuan Lu; Aakriti Gupta; Erica S. Spatz; Jiapeng Lu; Chenxi Huang; Jeph Herrin; Shuling Liu; Jingwei Yang; Chaoqun Wu; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Characterizing and assessing the prevalence, awareness, and treatment patterns of patients with isolated diastolic hypertension (IDH) can generate new knowledge and highlight opportunities to improve their care. Methods and Results We used data from the China PEACE (Patient‐centered Evaluative Assessment of Cardiac Events) Million Persons Project, which screened 2 351 035 participants aged 35 to 75 years between 2014 and 2018. IDH was defined as systolic and diastolic blood pressure of <140 and ≥90 mm Hg; awareness as self‐reported diagnosis of hypertension; and treatment as current use of antihypertensive medications. Of the 2 310 184 participants included (mean age 55.7 years; 59.5% women); 73 279 (3.2%) had IDH, of whom 63 112 (86.1%) were untreated, and only 6512 (10.3%) of the untreated were aware of having hypertension. When compared with normotensives, participants who were <60 years, men, at least college educated, had body mass index of >28 kg/m2, consumed alcohol, had diabetes mellitus, and prior cardiovascular events were more likely to have IDH (all P<0.01). Among those with IDH, higher likelihood of awareness was associated with increased age, women, college education, body mass index of >28 kg/m2, higher income, diabetes mellitus, prior cardiovascular events, and Central or Eastern region (all P<0.05). Most treated participants with IDH reported taking only 1 class of antihypertensive medication. Conclusions IDH affects a substantial number of people in China, however, few are aware of having hypertension and most treated participants are poorly managed, which suggests the need to improve the diagnosis and treatment of people with IDH.